A methodology for the analysis and improvement of a firm´s competitiveness - Contador, Jose Celso; Contador, Carlos Alberto; Carvalho, Marcius Fabius Henriques de; Contador, José Luiz (Revista de Ciências da Administração, 2006)
This paper presents a new methodology for the analysis of a group of companies, aiming at explaining and increasing a firm´s competitiveness. Based on the model of the fields and weapons of the competition, the methodology distinguishes between business and operational competitive strategies. The first consists of some of the 15 fields of the competition, and the latter consists of the weapons of the competition. Competitiveness is explained through the application of several mathematical variables. The influence of the competitive strategies is statistically evaluated using the Wilcoxon-Mann-Whitney non-parametric test, the t-test, and Pearson´s correlation. The methodology was applied to companies belonging to the textil e pole of Americana; one of the conclusions reached is that what explains competitiveness is the operational strategy rather than the business strategy. Therefore, to improve competitiveness, a company must intensify its focus on weapons that are relevant to the fields where it decided to compete.